Control Method of Diesel Locomotive Auxiliary Converter Based on DSP - GAO Lulu; LUO Guoyong; ZENG Minggao (Kongzhi Yu Xinxi Jishu)
It introduces the principle frame of diesel locomotive ACU hardware platform, and describes RS485 data communications standards based on MODBUS_RTU and a variable-frequency control. Aiming to the problems such as the communication link interference and the impact of instantaneous start motor on power supply system, an optimal design was performed to eliminate such interference, and a variable-frequency variable-voltage scheme was applied to reduce the impact of constant-frequency constant-voltage on the system. The test results prove that the diesel locomotive auxiliary converter with the proposed scheme has good output characteristics.